Evaluating the Diagnostic Value of the Tissue Hypoxia, Membrane Destruction and Undifferentiated Connective Tissue Dysplasia Markers in Young Children with Vesicouretheral Reflux - N.S. Lukyanenko; K.A. Kens; N.A. Petritsa (Zaslavsky O.Yu., 2016)
Introduction. The issue of congenital urinary defects in young children becomes more apparent due to the annual increase in the number of patients. One of the most frequent pathologies is vesicoureteral reflux. Today, there is a tendency to the increase in the number of microanomalies caused by the peculiarities of the connective tissue, which manifest with a complex of phenotypic features, and are considered as undifferentiated connective tissue dysplasia. This requires the search for high-sensitivity, specific, as well as noninvasive methods for the dynamic evaluation of the functional state of the renal parenchyma and prognosis of nephrosclerotic changes in undifferentiated connective tissue dysplasia in young children with vesicouretheral reflux. Aim. To establish the referent value of some indexes of the functional state of the renal parenchyma in young healthy children and to evaluate their informativeness and diagnostic value in children with vesicoureteral reflux associated with undifferentiated connective tissue dysplasia. Materials and methods. We have examined 50 children with vesicoureteral reflux degree II-IV associated with connective tissue dysplasia. Oxyprolin and markers of parenchymal tissue hypoxia, disorders of the functional state of the connective tissue of the renal parenchyma were determined in the urine. Discussion of the results. Tests chosen to characterize functional state of the renal parenchyma characteristics in children have mostly high and medium-high sensitivity in high specificity in the range of 82.5-98.0 %. The size of predictive value of both positive and negative results of selected tests in children with vesicoureteral reflux confirmed the effectiveness of diagnosing tissue hypoxia and violations of the functional state of the kidney parenchyma. Conclusions. There were proved the high sensitivity, specificity, predictive value and efficacy of the diagnosis of early disorders of the functional state and the development of sclerotic changes in renal parenchyma of children with vesicoureteral reflux associated with undifferentiated connective tissue dysplasia.